2010
DOI: 10.3390/w2040886
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Hydraulic and Water Quality Renovation Functions by Intermittent Aeration of Soil Treatment Areas in Onsite Wastewater Treatment Systems

Abstract: Abstract:We tested intermittent aeration of the soil treatment area (STA) of onsite wastewater treatment systems (OWTS) for its ability to restore and maintain STA hydraulic flow and improve the water quality functions of conventional OWTS. Evaluation was conducted on hydraulically-failed conventional OWTS at three state-owned medical group homes in Washington County, RI, USA. Testing was conducted in two phases, with Phase I (before intermittent soil aeration (ISA)) comprising the first 6 months of the study,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 11 publications
(22 reference statements)
0
2
0
Order By: Relevance
“…In previous studies we have shown that intermittent aeration of leachfield mesocosms receiving domestic STE have N removal rates ranging from 25 to 75%, depending on the soil type and dosing rates (Potts et al, 2004;Amador et al, 2007). More recently we have shown that N removal rates similar to those in the laboratory are observed in conventional OWTS under field conditions when intermittent aeration is used (Amador et al, 2010). We have hypothesized that intermittent aeration enhances N removal by promoting nitrification (during the aeration phase), followed by denitrification (as STE infiltrates and percolates through the soil), with net N losses attributed to N 2 and N 2 O produced by denitrification (Potts et al, 2004).…”
Section: Mechanisms Of Ammonium Transformation and Loss In Intermittementioning
confidence: 70%
“…In previous studies we have shown that intermittent aeration of leachfield mesocosms receiving domestic STE have N removal rates ranging from 25 to 75%, depending on the soil type and dosing rates (Potts et al, 2004;Amador et al, 2007). More recently we have shown that N removal rates similar to those in the laboratory are observed in conventional OWTS under field conditions when intermittent aeration is used (Amador et al, 2010). We have hypothesized that intermittent aeration enhances N removal by promoting nitrification (during the aeration phase), followed by denitrification (as STE infiltrates and percolates through the soil), with net N losses attributed to N 2 and N 2 O produced by denitrification (Potts et al, 2004).…”
Section: Mechanisms Of Ammonium Transformation and Loss In Intermittementioning
confidence: 70%
“…The headspace of mesocosms was either vented to the septic system leachfield of the house to simulate a conventional leachfield atmosphere (LEACH treatment) or was aerated intermittently with ambient air (AIR treatment) using a process that has been employed successfully to rejuvenate hydraulically-failed septic systems [12]. Each treatment was replicated three times.…”
Section: Aerationmentioning
confidence: 99%